Analysis and Assessment of Pulp Vitality of 102 Intrinsically Stained Teeth in Dogs. (March 2022) - Feigin, Kristina; Bell, Cindy; Shope, Bonnie; Henzel, Scott; Snyder, Christopher
Our prospective study analyzed clinical, radiographic, and histological characteristics of 102 intrinsically stained teeth. Sixty-nine dogs ranging from one to fifteen years of age were included in this study. Little more than half of the intrinsically stained teeth had no evidence of coronal injury (53.9%, 55/102). We found that most intrinsically stained teeth were histologically nonvital (87.6%, 85/97) and approximately 2/3 of these (57.7%, 56/97) had no histological endodontic or periodontal inflammation at the time of evaluation. Radiographic evidence of endodontic disease was present in 57% (58/102) of the intrinsically stained teeth. Radiographic evidence of periodontal disease was present in 48% (49/102) of intrinsically stained teeth and 28% (29/102) had radiographic evidence of tooth resorption. 18.6% (19/102) of intrinsically stained teeth were radiographically normal. Evidence of pulp necrosis was common in these intrinsically stained teeth, while only occasional teeth (12.4%, 12/97) had histologically confirmed pulpitis. All teeth with radiographic evidence of periapical lucency had pulp necrosis. Based on our histological findings, the majority of intrinsically stained teeth 87.6% are truly nonvital.